TRPC4 deletion elicits behavioral defects in sociability by dysregulating expression of microRNA-138-2 - Jee Young Seo; Hye-Ryeong Jo; Seung Hoon Lee; Do Gyeong Kim; Huiju Lee; Ye Lim Kim; Young In Choi; Sung Jun Jung; Hyeon Son (iScience, 2024)
Summary: To investigate whether the defects in transient receptor potential canonical 4 (TRPC4), which is strongly expressed in the hippocampus, are implicated in ASD, we examined the social behaviors of mice in which Trpc4 was deleted (Trpc4−/−). Trpc4−/− mice displayed the core symptoms of ASD, namely, social disability and repetitive behaviors. In microarray analysis of the hippocampus, microRNA (miR)-138-2, the precursor of miR-138, was upregulated in Trpc4−/− mice. We also found that binding of Matrin3 (MATR3), a selective miR-138-2 binding nuclear protein, to miR-138-2 was prominently enhanced, resulting in the downregulation of miR-138 in Trpc4−/− mice. Some parameters of the social defects and repetitive behaviors in the Trpc4−/− mice were rescued by increased miR-138 levels following miR-138-2 infusion in the hippocampus. Together, these results suggest that Trpc4 regulates some signaling components that oppose the development of social behavioral deficits through miR-138 and provide a potential therapeutic strategy for ASD.